The association of hidradenitis suppurativa with obstructive sleep apnea: A cross‐sectional study using the All of Us database - Samuel Yeroushalmi; Jared Liu; Mimi Chung; Kareem G. Elhage; Erin Bartholomew; Marwa Hakimi; Sugandh Kumar; Alexander Ildardashty; Haley B. Naik; Tina Bhutani; Wilson Liao (JEADV Clinical Practice, 2023)
Abstract Background Preliminary evidence shows a possible association between hidradenitis suppurativa (HS) and obstructive sleep apnea (OSA), which is associated with various cardiovascular comorbidities. Objectives To determine the odds of OSA among patients with HS compared with patients without HS. Methods We performed a cross‐sectional analysis using the All of Us research program database using electronic health records (EHR) and survey data from individual patient records extracted on 7 May 2022. Adult patients with available EHR records who either had at least one recorded diagnosis of HS determined by SNOMED‐CT code (HS cohort) or did not have a diagnosis (non‐HS cohort). The main outcome was a diagnosis of OSA as determined by SNOMED‐CT code. Demographic features, survey data, and relevant comorbidities were also collected. Results A total of 1647 patients with HS and 269,492 patients without HS were included. Of the HS patients, the mean age was 50.2 years, 79.0% were female, 39.8% were African American, 38.4% were White, and 17.4% were Hispanic or Latino. The prevalence of OSA in HS patients was 22.2% compared with 4.8% in non‐HS patients. Univariate and multivariate odds ratios of OSA between HS and non‐HS patients were 3.04 (95% confidence interval [CI]: 2.70–3.42) and 2.00 (95% CI: 1.72–2.33), respectively. The odds of OSA were highest in HS patients who were male, white, over 65 years of age, obese, and had hypertension, or hypothyroidism. Conclusions The odds of being affected by both HS and OSA are augmented by multiple demographic factors, including white race, male gender, obesity, hypertension, hypothyroidism, and age over 65. Longitudinal studies are needed to confirm these findings.